A Comparative Study Of Job Satisfaction Among Employees Working In National And Multinational Automobile Companies In Malaysia - Wu, Swee Ting (2006)
This is a comparative study to explore the differences in job satisfaction among employees working in multinational and national automobile companies in Malaysia. Call Number LB 1029.C37 S94 2006